Serum biomarkers for the evaluation of liver fibrosis: The need for better tests - Zeybel, Müjdat; İdilman, Ramazan (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Zeybel M, İdilman R. Serum biomarkers for the evaluation of liver fibrosis: the need for better tests. Turk J Gastroenterol 2018; 29: 377-8.